The research progress in the interaction between Candida albicans and cancers - Yu, Dalang; Liu, Zhiping (Frontiers in Microbiology, 2022)
Candida albicans(C.albicans) is an opportunistic pathogenic fungus, which tends to infect the host with low immune function including cancer patients. A growing number of studies have shown that C.albicans infection increases the host susceptability to cancer such as oral, gastric, and colorectal cancer. C.albicans may promote the development of cancer by damaging mucosal epithelium, inducing the production of carcinogens, triggering chronic inflammation including helper T17 cell immune response. In this paper, we aim to elaborate the potential role of C.albicans in the development of cancer and summarize the potential molecular mechanisms, so as to provide thereotical basis for prevention, diagnosis and treatment of cancers.